The perception of local community towards cultural and historical value of urban heritage tree in georgetown world heritage site (GWHS) - Abdul Aziz, Noor Azramalina; Mohd Ariffin, Noor Fazamimah; Mohamad, Nurul Nadiah; Hussain, Norhuzailin; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah; Ismail, Sumarni; Shaari, Nazlina; Abd Rahman, Khairul Aidil Azlin; Utaberta, Nangkula (Human Resources Management Academic Research Society (HRMARS), 2024)
A heritage tree is a large, old, individual tree attached with some unique values, considered irreplaceable. The unique values of heritage trees are called social-cultural values. Rapid development in a historical city has become a threat to the natural character of the World Heritage Site. The stakeholders need to understand the importance of the social-cultural value of urban heritage trees to preserve them. However, the urban heritage trees should be given more attention in the Georgetown World Heritage Site (GWHS). This study aims to evaluate the local community's perception of the cultural and historical value of urban heritage trees in GWHS. The quantitative method uses a survey technique. Two hundred (200) questionnaires were distributed to the local community. The data was analyzed using SPSS. Most respondents found that urban heritage trees in GWHS have cultural and historical value that benefit nature and the community.